Educational inequalities : difference and diversity in schools and higher education - Bhopal, Kalwant; Maylor, Uvanney (New York, NY : Routledge, 2014)
'While there is considerable literature on social inequality and education, there is little recent work which explores notions of difference and diversity in relation to'race,' class and gender. This edited text aims to bring together researchers in the field of education located across many international contexts such as the UK, Australia, USA, New Zealand and Europe. Contributors investigate the ways in which dominant perspectives on'difference,' intersectionality and institutional structures underpin and reinforce educational inequality in schools and higher education. They emphasize the importance of international perspectives and innovative methodological approaches to examining these areas, and seek to locate the dimensions of difference within recent theoretical discourses, with an emphasis on'race,' class and gender as key categories of analysis.'--
Includes bibliographical references and index.
Keywords: Educational equalization -- Cross-cultural studies; Education, Higher -- Social aspects -- Cross-cultural studies; Educational change -- Cross-cultural studies; Educational attainment -- Cross-cultural studies